A Brief Study of Master’s Degree Students’ Writing Skills Proficiency - Gurung, Raj Kumar (Humanities and Social Sciences Journal, 2022)
<>The main objective of this paper was to examine the academic writing skills of master’s degree students and equip them to write a research paper logically. The study was carried out to make the target groups feel the pivotal role of coherence and cohesion in writing. To analyze the writing skill, the qualitative approach was used as a major method although the quantitative approach was also sued partially. One of the findings of the study was that the target groups pointed out the traditional methods of teaching. About fifty respondents pointed out that there are no practical writing classes. Most of them realized that a research paper is a good combination of ideas organized and a coherent presentation of the thesis statement and methodology. Coherence and cohesion are the major factors of a research paper. They found that research paper writing is a challenging job.